Strategi Pengelolaan Ide dan Gagasan untuk UMKM Warung Bakso menuju Kesuksesan dalam Industri Kuliner - Suhendra, Suhendra; Margaret, Natasia Theofani; Banjar, Yefoni Valentina; Lubis, Putri Kemala Dewi (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to explore and analyze the strategy of managing ideas and ideas to increase profitability in Micro, Small and Medium Enterprises (MSMEs) meatball stalls. The method used for this research adopts a qualitative analysis approach and library research method. The data used in this research is secondary, which is obtained from books, journals, articles, and other sources relevant to the strategy of managing ideas and ideas in the culinary industry. The data collection technique is done by collecting reading material related to the problem under study. The results showed that Indonesian culinary MSMEs have a strong reputation and heritage, but are experiencing changes. To increase profitability and competitiveness, effective business planning and development strategies are essential. Business planning involves analyzing the industry, customers, and competitors, and identifying short- and long-term goals. Business development involves identifying opportunities, formulating business alternatives, selecting the best, implementing and evaluating. Idea and idea management strategies such as operational cost management, setting the right pricing policy, and improving operational efficiency are necessary to increase profitability.